Materiality and Managerial Techniques New Perspectives on Organizations, Artefacts and Practices (Technology, Work and Globalization, 2018)
This edited book examines the relationship between the materiality of artefacts and managerial techniques, combining the recent scholarly interest on socio-materiality with a focus on management. Exploring managerial techniques, the social and material tools used by actors to guide or facilitate collective activities, topics include their socio-materiality, performative dimension, role in managerial control, relationship to organisational space and relationship to organisational legitimacy. This volume particularly explores the valuation and legitimation practices or processes involving managerial techniques, their modalities, specificities and involvement in collective activity within organisations. The overall aim of the chapters is to explore in different ways and instances the way in which material artefacts are able to inscribe and enforce managerial action which affects daily work practices. .